Dynamic Governance in Creating a Safe Digital Space for Children in Bojonegoro Regency - Ratu Syifa; Ahmad Taufiq; Sri Kasiami (Jurnal Ilmiah Administrasi Publik, 2026)
The rapid expansion of digital technology presents significant challenges for local governments in ensuring child protection from harmful content and online risks. This study seeks to examine the application of Dynamic Governance principles : Thinking Ahead, Thinking Again, and Thinking Across in digital child protection initiatives within Bojonegoro Regency. Using a qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving key actors such as DP3AKB, the Communication and Information Office, schools, NGOs, media, parents, and children. The findings indicate that Thinking Ahead is reflected in digital literacy education, although it is not yet supported by comprehensive technical guidelines or long-term planning. Thinking Again appears through routine evaluations, but policy learning remains limited and occurs more strongly within families. Thinking Across demonstrates the existence of cross-sector collaboration, which remains coordinative rather than integrative. The study concludes that digital child protection efforts have been initiated, yet they have not fully demonstrated dynamic, adaptive, and collaborative governance.